Understanding Dwarfism's Identity Negotiation in the Face of Stigmatized Abominations of the Body - Arif Hidayat; Nurul Hasfi (Interaksi: Jurnal Ilmu Komunikasi, 2025)
Different physical conditions experienced by dwarf humans in Palak Siring Village often give rise to social stigma, even though every individual has the right to express and negotiate their identity despite bodily differences. This study aims to explore how dwarf humans negotiate their identities when facing stigma related to physical differences and how self-actualization is pursued as a pathway toward social acceptance and success. This research employs a qualitative descriptive approach using a case study method. Data were collected through in-depth interviews, participant observation, and document analysis involving three dwarf individuals as key informants. The analysis was guided by Identity Negotiation Theory to understand the processes through which informants construct self-concepts, manage social identities, and negotiate meaning in everyday interactions within community and work environments. The findings reveal that the informants interpret their different physical conditions as part of their identity and self-worth, shaping both personal self-concepts and social identities. In facing stigma and differing societal perceptions, informants actively negotiate their identities through various strategies such as accommodation, competition, avoidance, compromise, and collaboration. These negotiation processes enable them to gain social acceptance, reduce stigma, and demonstrate self-actualization through personal achievements. The study concludes that identity negotiation plays a crucial role in bridging social differences, allowing individuals with dwarfism to maintain dignity, achieve recognition, and foster mutual understanding within a pluralistic society. Theoretical implications highlight the relevance of Identity Negotiation Theory in disability and stigma studies, while practical implications emphasize the importance of inclusive communication practices and social awareness to reduce stigma toward persons with disabilities, particularly those with visible physical differences.